2018
DOI: 10.3332/ecancer.2018.835
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study on kilovoltage surface brachytherapy in conjunctival cancer: preliminary results

Abstract: IntroductionIn ocular conjunctival carcinoma after surgery, adjuvant treatment has a role and kilovoltage surface brachytherapy opens a new door for the range of therapeutic options.Materials and methodsBetween October 2014 and June 2017, at the National Institute of Neoplastic Diseases (INEN) from Peru, 39 patients with squamous cell carcinoma of ocular conjunctiva, T1–T3, resected, were selected to receive adjuvant treatment. The portable accelerator of 50-kV INTRABEAM (Carl Zeiss Meditec) was used, after lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…To our knowledge, we are the first group worldwide to report the outcomes of e-BT in this scenario. In addition to a previous publication regarding treatment safety and toxicity profile [ 23 ], these current results highlight the value of this approach, in matters of toxicity, disease control, and logistic advantage. The latter feature yields a special benefit, as high influx facilities struggle permanently in matters of extended waiting lists for EBRT slots [ 24 ].…”
Section: Discussionsupporting
confidence: 67%
“…To our knowledge, we are the first group worldwide to report the outcomes of e-BT in this scenario. In addition to a previous publication regarding treatment safety and toxicity profile [ 23 ], these current results highlight the value of this approach, in matters of toxicity, disease control, and logistic advantage. The latter feature yields a special benefit, as high influx facilities struggle permanently in matters of extended waiting lists for EBRT slots [ 24 ].…”
Section: Discussionsupporting
confidence: 67%
“…In consequence, we initiated a phase I/II study on adjuvant electronic brachytherapy for patients with resected squamous cell carcinoma of the ocular conjunctiva. At single doses between 18 and 22 Gy, we did not see any grade 2 or higher toxicity, which suggested that this therapeutic strategy may also be safe for patients with conjunctival lymphomas, where even lower doses were applied [ 34 ].…”
Section: Discussionmentioning
confidence: 99%